Pengembangan Aplikasi Mobile Learning Konstruksi Jalan dan Jembatan Untuk Optimalisasi Pembelajaran SMK Jurusan Bangunan Kota Surakarta - Kusuma, Fajar Indra; Subiyantari, Ansheila Rusyda; Dian, Imam Fahmi; Fatima, Izma (VOCATECH: Vocational Education and Technology Journal, 2025)
The integration of technology in education, particularly in Vocational High Schools (SMK), is increasingly necessary to support interactive and digital-based learning. This study aims to develop a mobile-based learning media application for the subject of road and bridge construction for students in the building engineering department of SMK. Based on preliminary observations and data, 86% of the 96 respondents stated that conventional teaching methods remain ineffective, and 96% expressed the need for more interactive media. This research uses the Research and Development (RD) method with the Alessi Trollip model, consisting of three stages: (1) Planning (needs analysis of students and teachers), (2) Design (development of user interface, curriculum content, and simulation features), and (3) Development (program implementation to produce a product ready for testing). Alpha testing involving media experts, subject matter experts, and practitioners yielded a rating of "Excellent" (score 85–100%). Meanwhile, beta testing with 96 students resulted in a score of 86.10%, indicating that the application is effective in enhancing understanding of the material through 3D simulation features, demonstration videos, and interactive quizzes. In conclusion, the application is suitable for implementation as an interactive learning solution in SMK, especially for technical subjects such as road and bridge construction. The implication is that the development of similar media can serve as a reference for educators in leveraging mobile technology to improve the quality of vocational education.